Injectable Multifunctional Drug Delivery System for Hard Tissue Regeneration under Inflammatory Microenvironments - Bordini, Ester A. F. (2021)
Engineering multifunctional hydrogel systems capable of amplifying the regenerative capacity of endogenous progenitor cells via localized presentation of therapeutics under tissue inflammation is central to the translation of effective strategies for hard tissue regeneration. Here, we loaded dexamethasone (DEX), a pleotropic drug with anti-inflammatory and mineralizing abilities, into aluminosilicate clay nanotubes (halloysite clay nanotubes (HNTs)) to engineer an injectable multifunctional drug delivery system based on photo-cross-linkable gelatin methacryloyl (GelMA) hydrogel. In detail, a series of hydrogels based on GelMA formulations containing distinct amounts of DEX-loaded nanotubes was analyzed for physicochemical and mechanical properties and kinetics of DEX release as well as compatibility with mesenchymal stem cells from human exfoliated deciduous teeth (SHEDs). The anti-inflammatory response and mineralization potential of the engineered hydrogels were determined in vitro and in vivo. DEX conjugation with HNTs was confirmed by FTIR analysis. The incorporation of DEX-loaded nanotubes enhanced the mechanical strength of GelMA with no effect on its degradation and swelling ratio. Scanning electron microscopy (SEM) images demonstrated the porous architecture of GelMA, which was not significantly altered by DEX-loaded nanotubes' (HNTs/DEX) incorporation. All GelMA formulations showed cytocompatibility with SHEDs (p < 0.05) regardless of the presence of HNTs or HNTs/DEX. However, the highest osteogenic cell differentiation was noticed with the addition of HNT/DEX 10% in GelMA formulations (p < 0.01). The controlled release of DEX over 7 days restored the expression of alkaline phosphatase and mineralization (p < 0.0001) in lipopolysaccharide (LPS)-stimulated SHEDs in vitro. Importantly, in vivo data revealed that DEX-loaded nanotube-modified GelMA (5.0% HNT/DEX 10%) led to enhanced bone formation after 6 weeks (p < 0.0001) compared to DEX-free formulations with a minimum localized inflammatory response after 7 days. Altogether, our findings show that the engineered DEX-loaded nanotube-modified hydrogel may possess great potential to trigger in situ mineralized tissue regeneration under inflammatory conditions.